The Forms of Historical Fiction - Shaw, Harry E. (Cornell University Press, 2023)
Harry Shaw’s aim is to promote a fuller understanding of nineteenth-century historical fiction by revealing its formal possibilities and limitations. His wide-ranging book establishes a typology of the ways in which history was used in prose fiction during the nineteenth century, examining major works by Sir Walter Scott—the first modern historical novelist—and by Balzac, Hugo, Anatole France, Eliot, Thackeray, Dickens, and Tolstoy.